Comparable survival in ischemic and nonischemic cardiomyopathy secondary to ventricular tachyarrhythmias and aborted cardiac arrest. Issue 4 (June 2019) - Rusnak, Jonas; Behnes, Michael; Schupp, Tobias; Weiß, Christel; Nienaber, Christoph; Lang, Siegfried; Reiser, Linda; Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; et al.
Abstract : Objectives: The study sought to assess the impact of ischemic cardiomyopathy (ICMP) and nonischemic cardiomyopathy (NICMP) on secondary survival in patients presenting with ventricular tachyarrhythmias and aborted sudden cardiac arrest (SCA). Background: Data regarding the outcome of patients with ICMP or NICMP presenting with ventricular tachyarrhythmias or aborted SCA is limited. Patients and methods: A large retrospective registry was used including all consecutive patients presenting with ventricular tachycardia (VT), ventricular fibrillation (VF), or aborted SCA on admission from 2002 to 2016. ICMP and NICMP were compared applying univariable correlation models and propensity score matching for evaluation of the primary prognostic end point defined as long-term all-cause mortality at 2.5 years. Secondary end points were all-cause mortality at 30 days, at index hospitalization, and after discharge; the composite end point of recurrent ventricular tachyarrhythmias, cardiac death at 24 h, and appropriate implantable cardioverter defibrillator (ICD) therapy; and finally, rehospitalization related to ventricular tachyarrhythmias. Results: A total of 276 matched patients were included. The rates of VT and VF were similar in both groups (VT: 75 vs. 73%; VF: 23 vs. 22%). At 2.5 years, no differences were found regarding the primary end point of all-cause mortality in both patients with ICMP and NICMP (mortality rate: 33 vs. 32%; log-rank P =0.898). Similar survival was present irrespective of the presence of acute myocardial infarction, underlying ventricular tachyarhythmia (VT/VF), left ventricular dysfunction, and an activated ICD. Furthermore, no significant differences could be seen regarding secondary end points of all-cause mortality at 30 days, at index hospitalization, and after discharge; the composite end point of recurrent ventricular tachyarrhythmias, cardiac death at 24 h, and appropriate ICD interrogation; and finally rehospitalization related to ventricular tachyarrhythmias. Conclusion: Both ICMP and NICMP reveal comparable secondary survival after episodes of ventricular tachyarrhythmias or SCA on admission.